2018
DOI: 10.21608/nssj.2018.30721
|View full text |Cite
|
Sign up to set email alerts
|

U-Minerals and Ree Distribution, Paragenesis and Provenance, Um Bogma Formation Southwestern Sinai, Egypt

Abstract: The lower Carboniferous sediments at SW Sinai comprises four stratigraghic formations from bottom: Um Bogma, El Hashash, Magharet El Maiah and Abu Zarab formations. The uranium bearing sediments are mainly confined and associated with Um Bogma Formation. The stratigraphic sections exposed at the six localities, (Talet Selim, Nasib, Abu Thor, Allouga, Abu Hamata and El Sahu), were studied in detail. These are exposed within a low basinal shaped area that was affected by several fault sets comprising strike-slip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…• Um-Bogma Formation: This formation can be regarded as a poly-mineralized rock unit including (U, Th, Cu, and REEs,) (Alshami, 2018 andAlkhateeb et al, 2019). It can be classified into three members:…”
Section: Geological Outlinesmentioning
confidence: 99%
“…• Um-Bogma Formation: This formation can be regarded as a poly-mineralized rock unit including (U, Th, Cu, and REEs,) (Alshami, 2018 andAlkhateeb et al, 2019). It can be classified into three members:…”
Section: Geological Outlinesmentioning
confidence: 99%
“…The NWtrending faults controlled the high uranium concentration at Wadi Nasieb and Talet Seliem, whereas the NE-trending faults controlled the U-concentrations at Baba. The authors [21] recorded that Allouga and Abu Thor area located within a low basinal-shaped area that was affected by several fault sets comprising strike-slip and step faults, which to some degree helped the localization of the U and Au minerals.…”
Section: Abu Thora Formationmentioning
confidence: 99%
“…Weissbrod (1969) gives Um Bogma Formation (8.5-66m) to the carbonat e rocks. Alshami (2017) reported that Um Bogma Formation comprises seven facies, these facies are Fe-Mn ore, gibbsite bearing sediments, claystone, marl, dolostone, shale and ferruginous siltstone. Soliman and Fetouh (1969) subdivided the clastic sediments into El Hashash, Magharet El Maiah and Abu Zarab formations.…”
Section: Lower Carboniferous Sedimentsmentioning
confidence: 99%